The Effect of the Effectiveness of the Audit Committee toward the Quality of Financial Reports - Gunawan Hutomo Mandala Putra; Azwir Nasir; Novita Indrawati (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aimed to analyze the effect of the effectiveness of the audit committee in terms of expertise, charter, total of audit committees, total of audit committee meetings which are expected to have an influence on the quality of financial reports. This research was conducted through quantitative methods using secondary data. Secondary data consisted of data on the date of issuance of the company's financial reports on the IDX website and annual reports of companies that had been listed on the IDX in 2018. The research population was all manufacturing companies listed on the IDX. The sample selection procedure used purposive sampling method with a total sample size of 96 companies and the analysis technique used was multiple regression. The results proved that the expertise of the audit committee, the audit committee charter, the total of audit committees and the audit committee meetings had a significant effect on the quality of financial reports.